Keputusan Pembelian Produk Ayam Nelongso Melalui Ulasan di Media Sosial di Kalangan Mahasiswa UIN Sunan Ampel Surabaya - Asfiana, Risfi; Dwi Enjelika, Mita; Aulia Putri Desna, Mega; Pangestu, Rizky; Trisna, M. Adi (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to describe the influence of reviews on social media on purchasing decisions for Ayam Nelongso products among students at UIN Sunan Ampel Surabaya. In the era of globalization and technological advances, social media has become an important platform for disseminating information and influencing consumer behavior. The method used is quantitative by collecting data through questionnaires distributed to students who are active on social media. The research results show that the credibility of reviews, social interactions, and recommendations from friends greatly influence purchasing decisions. This research also reveals the importance of effective marketing strategies through social media to increase customer satisfaction and loyalty. It is hoped that these findings can provide insight for culinary business people in understanding consumer behavior and utilizing social media as an effective marketing tool.